ATTITUDES AND PERCEPTIONS OF USING ZOOM: A SURVEY OF CAMBODIAN UNIVERSITY STUDENTS - Kassy Sey; Sereyrath Em (Asosiasi Dosen Perguruan Tinggi Islam, 2023)
Due to the COVID-19 pandemic, many Cambodian schools and universities have been forced to move their educational activities from face-to-face to online modes. Those universities and schools have been using some online applications like Zoom as their teaching and learning delivery platform. Consequently, there have been challenges to the use of the app. The current study employed a quantitative design, and it was conducted at a Cambodian university with a total of 50 students. The study aimed to investigate those students' attitudes and perceptions toward using the Zoom platform for their online learning. The results showed that the students had negative attitudes toward the use of Zoom as well as low perceptions of using Zoom during the pandemic. Future studies should be conducted with a bigger sample size at other universities across the country. A qualitative study or a mixed-methods design is also recommended. Teachers’ attitudes and perceptions of using Zoom for teaching might also be welcome.